Problems of increasing legal regulation efficiency of personnel management - N. B. Efimochkina (Вестник университета, 2019)
Currently, the effective organization of management of personnel labor consists in establishment of organizational and economic, social and psychological and legal relations of the subject and object of management - the head and the employee. These relations are based on legal principles, methods and forms of influence on the interests, behavior and activities of employees, ensuring the legitimacy of their activities and allowing the maximum use of the full potential of human resources of the organization. At the same time, the practice of Russian organizations and enterprises shows, that there are significant problem areas in the field of local law enforcement. The problems of legal support in the personnel management system, most often present in domestic companies, have been considered in the article.